Analisa Pengaruh Berat Roller CVT 15 Gram, 10 Gram dan 8 Gram Terhadap Daya Dan Torsi Pada Sepeda Motor All New Vario 149 CC Dengan Metode Pengujian Dynotest - Mourad Rif’at Dien Yahya; Rizal Hanifi; Iman Dirja (Peneliti.net, 2023)
One of the supporting factors for automatic motorcycle to get good performance is the roller. Many users do not know about the influence of the roller on torque and power. In this final project aims to determine the effect of roller weight variations on motorcycle torque and determine the effect of roller weight variations on motorcycle power. This final project research uses automatic transmission motorcycles, namely Honda All New Vario 149cc motorcycles in 2018. In this test using three types of roller weight variations aims to determine the effect of using the CVT on the power and torque of the Honda All New Vario 149cc motorcycles, namely roller weight 15 grams, roller weight 10 grams and roller weight 8 grams using the dynotest method and using a tool called a dynamometer. From the test results of the dynamometer tool on the 15 gram roller test it produces a maximum power of 10.11 HP at 8000 RPM and produces a maximum torque of 31.5 N.m at 2000 RPM, on the 10 gram roller test it produces a maximum power of 10.9 HP at 8000 RPM and produces a maximum torque of 31.9 N.m at 2000 RPM and in the 8 gram roller test produces a maximum power of 11.22 HP at 8000 RPM and produces a torque of 22.9 N.m. The results of this study resulted in a comparison of the three rollers by showing the effect on the weight of the roller used on the automatic motorcycle CVT